The fast forward MBA in marketing - Murphy, Dallas (Fast forward MBA series, 1997)
In this resource you'll find clear, concise coverage of the complete range of essential marketing topics in a format designed especially for people who need answers quickly. You'll also find cutting-edge ideas from highly regarded thinkers and doers and the world's best MBA programs.